Multi-scale Simulations of Metal-Semiconductor Nanoscale Contacts. (September 2015) - Aldegunde, M; Hepplestone, S P; Sushko, P V; Kalna, K
Abstract: An electron transport simulations via a metal-semiconductor interface is carried out using multi-scale approach by coupling ab-initio calculations with 3D finite element ensemble Monte Carlo technique. The density functional theory calculations of the Mo/GaAs (001) interface show electronic properties of semiconductor dramatically change close to the interface having a strong impact on the transport. Tunnelling barrier lowers and widens due to a band gap narrowing near the interface reducing resistivity by more than one order of magnitude: from 2.1 × 10 -8 Ω.cm 2 to 4.7 × 10 -10 Ω.cm 2 . The dependence of electron effective mass from the distance to the interface also plays a role bringing resistivity to 7.9 × 10 -10 Ω.cm 2 .